Broad but restricted detection of malacosporeans in a Neotropical cradle of diversification. Issue 5 (10th April 2021) - Naldoni, Juliana; Okamura, Beth; Hartikainen, Hanna; Corrêa, Lincoln L.; Adriano, Edson A.
Abstract: This study undertook the first investigation of malacosporean infections in Neotropical fish. We used polymerase chain reaction detection with a primer set generally targeting known malacosporeans to assay for infection in the kidney of 146 fish in 21 species belonging to 12 families collected from two areas in the Amazon Basin. Infections were found in 13 fish variously belonging to seven species in six families and included the first identification of a malacosporean infection in cartilaginous fish (a freshwater stingray). Based on ssrDNA, all infections represented a single Buddenbrockia species ( Buddenbrockia sp. E) that demonstrates an exceptionally broad range of fish species infected, and countered our expectations of high Neotropical malacosporean diversity. Infections were characterized at varying and often high prevalences in fish species but sample sizes were small. Ascertaining whether highly divergent malacosporeans have not been detected by current primers, and more comprehensive sampling may reveal whether malacosporeans are truly as species poor in the Amazon Basin as present data suggest. Our results prompt speculations about evolutionary scenarios including introduction via marine incursions and patterns of host use over time.